Proceedings of the 2nd International Conference on Experimental and Computational Mechanics in Engineering ICECME 2020, Banda Aceh, October 13–14 - Tanda, Maria Giovanna; Chiapponi, Luca (Singapore Springer, 2021)
This book gathers a selection of peer-reviewed papers presented at the 2nd International Conference on Experimental and Computational Mechanics in Engineering (ICECME 2020), held as a virtual conference and organized by Universitas Syiah Kuala, Banda Aceh, Indonesia, on 13–14 October 2020. The contributions, prepared by international scientists and engineers, cover the latest advances in computational mechanics, metallurgy and material science, energy systems, manufacturing processing systems, industrial and system engineering, biomechanics, artificial intelligence, micro/nano-engineering, micro-electro-mechanical system, machine learning, mechatronics, and engineering design. The book is intended for academics, including graduate students and researchers, as well as industrial practitioners working in the areas of experimental and computational mechanics.
Effect of densification pressure on physical and combustion properties of binderless briquettes made from rice-husk and coffee-pulp -- Characteristics of lightweight bricks composed of clay and diatomite -- Thermal characteristics of oil palm wood and ramie fiber as raw materials for thermal insulation bio board -- Effect of Soil Composition on the Corrosion Rate of Underground Water Distribution Pipes in Natural Environment -- Finite Element Model of Magnetic Induction Tomography for Low Conductivity Sample -- Airside heat transfer and pressure drop on the spiral finned-tube compact heat exchanger with sharp turns -- Preparation of chitosan-silver nanoparticles immobilized onto pumice for antibacterial testing against Eschericia coli -- Study of the effect sudu length on electricity power generated by wind speed In Banda Aceh beach.
Electronic reproduction
Keywords: Mechanics, Applied; Continuum mechanics; Mathematics -- Data processing; Engineering Mechanics; Electronic books